Automatic whiteboard cleaner / Haziq Syakir Ismail and Hazriel Faizal Pahroraji - Ismail, Haziq Syakir; Pahroraji, Hazriel Faizal (School of Mechanical Engineering, 2023)
The name of this project is Automatic Whiteboard Cleaner. This idea is inspired when students or teachers leave the classroom and forget to clean the whiteboard because they are rushing to go home. From there, the project is to make it easier for students or teachers to clean the whiteboard. There are some problems with making this project available in all schools, universities, or offices. For example, this project needs an electric power supply when it works. Therefore, this project needs a power supply to do the work. The objective of this project is to help people clean the whiteboard with a simple and easier method. In conclusion, hopefully, this project can make it easier to erase the whiteboard and use it in the classroom, school, office, or other place that uses the whiteboard for presentation. Therefore, demand for this project will increase in the industry.